ОРГ АНІЗАЦІЯ ДИСТАНЦІЙ НОГО КУРСУ АНГЛІЙ СЬКОЇ МОВИ ДЛЯ САМОСТІЙ НОЇ РБОТИ МАЙБУТНІХ ЕКОНОМІ СТІ В - Asoyants, P; Byelyen`ka, T (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the problem of organization of the process of teaching English for specific purposes of future economists with the help of the distance course. The author describes the technology of creation and further usage of that course, its role and place in the teachinglearning process.